(untitled) (Journal of Global Accounting, 2025)
The study examined the effect of firm profitability on environmental disclosure of listed manufacturing firms in Nigeria. The specific objective was to examine the effect of return on asset on Environmental Disclosure Index. The study adopted ex-post facto research design. The population comprised 42 listed manufacturing firms in Nigeria. A sample size of 30 was chosen using purposive sampling technique. The study collected secondary data from the firms’ annual reports over a thirteen year period from 2012-2024. Descriptive test was used to summarise the data while panel least square regression was used to test the hypotheses. It was found that firm profitability has a significant and positive effect on environmental disclosure of manufacturing firms in Nigeria (β = 0.6101, p = 0.0010). In conclusion, structural attribute of firms particularly those tied to performance carry meaningful implications for how firms respond to environmental concerns. The study recommends that managing directors and internal sustainability teams of profitable manufacturing firms should institutionalize environmental reporting as part of their corporate performance communication, leveraging available profits to invest in structured disclosure systems and third-party assurance mechanisms that enhance credibility.